Piezoelectric Energy Harvesting Characteristics of Barium Titanate Based Composite Laminates under Cyclic Concentrated Loads - Narita, Fumio; Zhu, Xiaolong; Shindo, Yasuhide (Journal of Composites and Biodegradable Polymers, 2017)
We investigate the dynamic electromechanical behavior in barium titanate (BT) based composite cantilevers under cyclic concentrated loads in a combined numerical and experimental approach. The laminated composite cantilever consists of the BT and copper (Cu) layers, and the BT layer has sensing and driving electrodes. The output voltage of the cantilevers due to cyclic bending were calculated by three dimensional finite element method. The output voltage was then measured, and numerical simulations were compared with test results to verify the finite element model. The influences of sensing electrode geometry and load resistance on the dynamic electromechanical fields were examined in detail.